Respuesta :
Answer:
1 real root 2 imaginary roots
Step-by-step explanation:
f(x) = x^3 + 5x^2 + x + 5
Set equal to zero to find the zeros
0 = x^3 + 5x^2 + x + 5
Factor by grouping
0 = x^2( x+5) + 1( x+5)
0 = (x+5) ( x^2+1)
Using the zero product property
x+5 =0 x^2+1 =0
x=-5 x^2 = -1
x=-5 x = ±i
1 real root 2 imaginary roots
Answer:
1 real root 2 imaginary roots
Step-by-step explanation:
f(x) = x^3 + 5x^2 + x + 5
Set equal to zero to find the zeros
0 = x^3 + 5x^2 + x + 5
Factor by grouping
0 = x^2( x+5) + 1( x+5)
0 = (x+5) ( x^2+1)
Using the zero product property
x+5 =0 x^2+1 =0
x=-5 x^2 = -1
x=-5 x = ±i
1 real root 2 imaginary roots